A case of adrenal myelolipoma mimicking pheocromocytoma (2001)
A 34 year-old hypertensive para 2 + 0 (1 alive) woman, was found to have right suprarenal mass during routine ante-natal investigation. The suprarenal mass, which was initially diagnosed as phaeochromocytoma was excised was found at histology to be myelolipoma. The radiological investigations and appearances (compared with phaeochromocytoma where necessary) have been discussed. The complications, differential diagnoses and treatment were mentioned.